A 21st Century Debate on Science and Religion. - Khaili, Shiva (Cambridge Scholars Publishing, 2017)
The progress of modern science and technology has led to remarkable insights into the nature of the universe and of human life. These insights have challenged and transformed former traditional worldviews and narratives. This book explores and addresses the challenges that arise at the interface of science and religion in the 21st century. How does science affect the way that religion is perceived? Do modern scientific findings confirm or invalidate the perspective of faith? How does science lead religious persons to revise the way they understand their faith and its practices? Is a mutually r.